Advanced Bilirubin Measurement by a Photometric Method - Penhaker, M.; Kasik, V.; Hrvolova, B. (Elektronika ir Elektrotechnika, 2013)
This paper describes the design of an electronic instrument for measuring bilirubin by the optical method of light transmission through the skin. There was the knowledge of light transmission and absorption on a specific tissue compartment applied. The relevant skin photo-diagnostics handle 450nm - green and 575nm- blue monochromatic light. The registration of transmitted light of different frequency combinations presents the bilirubin quantity in human body by a non-invasive way. This used device was successfully tested and relevantly confronted with accurate laboratory instruments used for bilirubin measurements. The proposed device is more than ten times cheaper and easy to use. That provides reliable care after newborns within the postnatal care. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.3696